Open access indicators: sources and tools - Borrego, Ángel (Anuario ThinkEPI, 2022)
Determining the percentage of open access publications available is the most pragmatic indicator for measuring the concreteness of open science policies and can be found in most plans in this field. This note offers a review of the literature published in the last decade about the evolution of open access to the scientific literature and the analysis of open access indicators developed in different countries. The results show that, when creating an open access indicator, it is necessary to make decisions regarding the collection of documents on which the calculation will be carried out, the tool that will be used to determine the availability of open access documents, the definition and typologies of open access being studied, the possible inclusion of additional sources of information, aspects related to timing, and the publication of the documentation necessary to guarantee the reproducibility of the indicator.
Keywords: Open access; Crossref; Indicators; Monitoring; Repositories; Unpaywall